PROBLEMATIKA DAN ALTERNATIF SOLUSI PENGATURAN INDUSTRI ROKOK DAN PRILAKU MEROKOK - Hardisman Hardisman (Andalas University, Faculty of Public Health, 2009)
Tobacco and cigarette problems in Indonesia are quite problematic. Tobacco industries have significant impact on Indonesian economic through creating employment opportunities informing and manufacturing sectors. The government also gains significant revenue from taxes on tobacco production and trade. Due to these economic benefits. Indonesia does not have adequate regulation for tobacco control. However, the prevalence tobacco consumption is high. This condition causes high prevalence of many severe diseases such as cardiovascular, respiratory and cancer which leads to high morbidity and mortality. Even, if we compare the economic benefits and cost for the health problems, the cost for negative impact is far more than the benefits. Based on these evidences. Indonesia should control tobacco production. Manufacture and trade. Some efforts should be done such as maintaining, taxes rate in current level, advertising regulation. Health warning on cigarette package, education campaign, free smoking in public spaces, create morejob opportunities and law enforcement.